Relationship between tax auditing, tax evasion, and corporate tax revenue in mining companies in the Puno region - Quinto Cutipa, Jose Luis (2025)
Objective: To analyze the relationship between tax audits, tax evasion, and corporate tax revenue in mining companies in the Puno region. Methods: A quantitative, non-experimental, cross-sectional, and correlational study with a sample of 45 mining companies. Statistical analysis was performed using Spearman’s rank correlation coefficient. Results: A moderate positive correlation was found between tax audits and tax evasion (ρ = 0.54), suggesting greater detection of evasive practices in contexts of increased tax oversight. Similarly, a moderate positive correlation was observed between tax evasion and tax collection (ρ = 0.37), as well as between tax audits and corporate tax revenue (ρ = 0.63), indicating that more intensive audits are associated with improved collection performance. Conclusion: The results show that tax audits are statistically associated with both the identification of evasive practices and tax collection performance in the mining sector in Puno.